ANALISIS MODEL DEEP DIALOGUE DALAM PENDIDIKAN AGAMA ISLAM UNTUK PENGEMBANGAN KETERAMPILAN BERPIKIR KRITIS DI ERA DIGITAL - Ali, Muhamad Mauris Faruqi; Syahidin, Syahidin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
In the digital era, critical thinking skills have become an indispensable competency to face global challenges and filter abundant information. The Deep Dialogue model focuses on deep interactions between teachers and students, designed to stimulate analytical, reflective, and evaluative thinking. This article reviews various literature sources that discuss the application of this model in various educational contexts. Findings from the literature study show that the Deep Dialogue model can strengthen students' abilities in critical thinking, especially in terms of analyzing arguments, solving problems, and evaluating information better. However, to achieve full effectiveness, teachers are required to facilitate in-depth dialogue and use supportive digital technology. This research concludes that the Deep Dialogue model can be a relevant and effective learning strategy for developing critical thinking skills needed to face the challenges of the information age.